Sports training in virtual reality to improve response behavior in karate kumite with transfer to real world - Witte, Kerstin; Droste, Melina; Ritter, Yvonne; Emmermacher, Peter; Masik, Steffen; Bürger, Dan; Petri, Katharina (Frontiers in Virtual Reality, 2022)
Virtual reality (VR) training has become valuable in sports to improve motor behavior and train specific situations under standardized conditions. However, studies comparing conventional training with VR training are rare, especially for advanced athletes. Furthermore, it remains unclear whether the performance improvement achieved through VR training can be transferred to the real world (RW). Therefore, we present a study analyzing sports-specific response training using a head-mounted display (HMD) combined with conventional training and its transfer to RW. In ten training sessions over six weeks, a VR training group (VRG, n=15) performed virtual karate training (10 min) combined with a conventional training (80 min), while a conventional training group (CG, n=12) conducted only conventional training (90 min) at the same time. The VR training consisted of the athlete responding to various karate attacks performed by a virtual opponent in a karate-specific manner. The study design included a pretest, an intermediate test (after 5 training sessions), and a posttest. We analyzed sports-specific response behavior concerning the competition-relevant karate attacks Gyaku-Zuki jodan (GZj) and Kizami-Zuki (KZ) using the parameters ‘response time’, and the ‘response quality’ when the athletes had to react to attacks of a virtual opponent in VR and a real opponent in RW. For the parameter ‘response time’, improvements were detected only for the VRG in VR concerning GZj and KZ. For the parameter ‘response quality’ for both groups, no improvements could be found. Furthermore, athletes provided positive feedback regarding the integration of VR training into conventional training.